The Influence of Interpersonal Communication Skills, Self-Efficacy, and Public Perception Towards the Glass Ceiling Phenomenon - Haris Herdiansyah; Paradilla Karisma Putri (Eduvest - Journal of Universal Studies, 2024)
The purpose of this quantitative research study is to determine the influence of Interpersonal Communication Skills, Self-Efficacy, and Public Perception towards The Glass Ceiling Phenomenon. There are four hypotheses in this study, 1. H1: There is no influence of interpersonal communication skills towards the glass ceiling phenomenon. 2. H2: There is an influence of self-efficacy towards the glass ceiling phenomenon. 3. H3: There is an influence of public perception towards the glass ceiling phenomenon. and 4. H4 There is a simultaneous influence of interpersonal communication skills, self-efficacy, and public perception towards the glass ceiling phenomenon. This study involved 189 respondents who matched the criteria of respondents needed by the researcher. The sampling technique used is convenience sampling. The results of this study show that the independent variables can have an effect of 0.822 or 82.2% towards the dependent variable. In addition, interpersonal communication skills have a negative influence towards the glass ceiling phenomenon of 0.047 or 4.7%, self-efficacy has an influence towards the glass ceiling phenomenon of 0.628 or 62.8%, and public perception influences 0,257 or 25.7% on work pressure.